Dangers of systemic interlock - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Extension alternatives in tropical Africa by Jon Moris 185pp 1991 UKL9.95 ISBN 0 85003 105 2 published by Overseas Development Institute Regent's College, Inner Circle Regent's Park, London NW1 4NS UK